Review Of Brain Lesion Detection And Classification Using Neuroimaging Analysis Techniques - Mohd Saad, Norhashimah; Abu Bakar, Syed Abdul Rahman Syed; Muda, Ahmad Sobri; Mokjib, Musa Mohd (Sains Humanika, 2015)
-